2003
DOI: 10.4049/jimmunol.170.2.703
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Lymphopoiesis and Altered B Cell Subpopulations in Mice Overexpressing Lnk Adaptor Protein

Abstract: Lnk is an adaptor protein expressed primarily in lymphocytes and hemopoietic precursor cells. Marked expansion of B lineage cells occurs in lnk−/− mice, indicating that Lnk regulates B cell production by negatively controlling pro-B cell expansion. In addition, lnk−/− hemopoietic precursors have an advantage in repopulating the hemopoietic system of irradiated host animals. In this study, we show that Lnk overexpression results in impaired expansion of lymphoid precursor cells and altered mature B cell subpopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…These observations present a reasonable synonym with the negative regulation by Lnk in c-Kit signals (14,37). In contrast, positive regulatory roles for SH2-B have been demonstrated in SH2-B Ϫ/Ϫ mice (13).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These observations present a reasonable synonym with the negative regulation by Lnk in c-Kit signals (14,37). In contrast, positive regulatory roles for SH2-B have been demonstrated in SH2-B Ϫ/Ϫ mice (13).…”
Section: Discussionmentioning
confidence: 84%
“…Increased plasma levels of leptin and adiponectin in APS ؊/؊ mice. Leptin and adiponectin, both major adipocyte secretory proteins, are thought to play important roles in glucose homeostasis and insulin resistance (37)(38)(39)(40). Plasma concentrations of leptin and adiponectin in APS Ϫ/Ϫ mice were significantly higher than concentrations in APS ϩ/ϩ mice ( Fig.…”
Section: Diabetes Vol 52 November 2003mentioning
confidence: 99%
“…SH4B3 overproduction in lymphoid precursors resulted in a reduction in the number of both B and T cells, whereas the lack of the SH4B3 gene showed enhanced B-cell production. 29 The association of rs1678542/KIF5A variant with MS, uncovered for the first time in this work, was first associated with RA in European populations. 18,30 The rs1678542/KIF5A is located 194 kb apart from the rs703842/methyltransferase-like protein 1 3 0 UTR with a linkage disequilibrium r 2 of 0.184.…”
Section: Kif5a Cd226 and Sh2b3 Variants Associate With Ms A Alcina Ementioning
confidence: 65%
“…Therefore, Lnk may negatively regulate signaling pathways originating from multiple cytokine receptors through a similar mechanism. Interestingly, the conserved tyrosine near the C-terminus of Lnk, Y536, is dispensable for the negative regulatory roles of Lnk in lymphocyte development 25 and Tpo-mediated megakaryocytopoiesis. 11 In contrast, we found that Y536 is important, but not required, for modulating Epo-dependent 32D cell proliferation or erythroblast survival.…”
Section: Lnk Induces Erythroblast Apoptosis In the Absence Of Cell Cymentioning
confidence: 99%